Detection of DNA adducts derived from the tobacco carcinogens, benzo[a]pyrene and dibenzo[def, p]chrysene in human oral buccal cells. (24th June 2022) - Chen, Kun-Ming; Sun, Yuan-Wan; Krebs, Nicolle M; Sun, Dongxiao; Krzeminski, Jacek; Reinhart, Lisa; Gowda, Krishne; Amin, Shantu; Mallery, Susan; Richie, John P; El-Bayoumy, Karam
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are recognized as potential etiological agents in the development of oral cancer in smokers. In particular, benzo[ a ]pyrene (B[ a ]P) and dibenzo[ def, p ]chrysene (DB[ a, l ]P) are detected in cigarette smoke and the environment and can induce DNA damage, mutagenesis and carcinogenesis in the oral cavity of rodents. Consequently, DNA adducts are regarded as the most direct markers of genotoxicity and can be used as biomarkers of cancer risk. Thus, this study used LC-MS/MS analysis with isotope labeled internal standard to detect and quantify DNA adducts derived from B[ a ]P and DB[ a, l ]P in buccal cells of cigarette smokers and non-smokers. Participants in this study include 21 smokers and 16 non-smokers. Our data are the first to report that levels (mean ± SD) of BPDE-N 2 -dG were significantly ( P < 0.001) higher in smokers (20.18 ± 8.40 adducts/10 8 dG) than in non-smokers (0.84 ± 1.02 adducts/10 8 dG). Likewise, levels of DBPDE-N 6 -dA in smokers (5.49 ± 3.41 adducts/10 8 dA) were significantly higher ( P = 0.019) than non-smokers (2.76 ± 2.29 adducts/10 8 dA). Collectively, the results of this clinical study support that PAHs in tobacco smoke can contribute to the development of oral cancer in humans. Abstract : We demonstrated for the first time that levels of BPDE-N 2 -dG and DBPDE-N 6 -dA were significantly higher in smokers than non-smokers. Our results support that PAHs in tobacco smoke can contribute to the development of oral cancer in humans. Graphical Abstract: